Studi Simulasi Konseptual Kinerja Filter Koaleser Berbasis Tandan Kosong Kelapa Sawit (TKKS) untuk Pemisahan Biodiesel-Air - Laudi Adytia Pratama; Hafshah Dwiyanti Sutopo; Oktrison; Harmiwati NH (REACTOR: Journal of Research on Chemistry and Engineering, 2026)
This study aims to theoretically evaluate the performance of a liquid-liquid (biodiesel-water) separation system using an Oil Palm Empty Fruit Bunch (OPEFB)-based coalescer filter through a conceptual computational simulation approach. The separation design evaluation was conducted using SuperPro Designer software in batch operation mode with key operating conditions set at a temperature of 60°C. The modelling covered the entire stages, starting from the transesterification reactor, water washing, to the final separation in the coalescer filter unit (P-5). The equipment's performance was evaluated based on the mass fraction profile of the final product compared to the waste stream content. The simulation model projected that the OPEFB coalescer filter shows potential to operate as a heavy and light phase separator based on ideal thermodynamic assumptions. The conceptual product stream composition was dominated by Fatty Acid Methyl Ester (FAME) approaching 100% (>99.99%), with a theoretical water separation efficiency reaching 99.989%, while water, methanol, glycerol, and residual catalyst were comprehensively isolated into the heavy phase (waste) stream. It must be explicitly noted that this is a preliminary simulation study; no physical OPEFB coalescer has been fabricated or experimentally tested, and no analytical confirmation of the critical biodiesel-quality parameters has been conducted. The design of the OPEFB coalescer filter is theoretically feasible in separating post-washing biodiesel-water emulsions, highlighting the necessity to proceed to the physical fabrication and empirical testing stages for actual process validation.